Patchouli Alcohol Improves the Integrity of the Blood-Spinal Cord Barrier by Inhibiting Endoplasmic Reticulum Stress Through the Akt/CHOP/Caspase-3 Pathway Following Spinal Cord Injury - Huang, Chongan; Zhang, Weiqi; Chu, FeiFan; Qian, Hao; Wang, Yining; Qi, Fangzhou; Ye, Mengke; Zhou, Jiaying; Lin, Zhi; Dong, ChenLin; Wang, Xiangyang; Wang, Qingqing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Spinal cord injury (SCI) is a destructive and complex disorder of the central nervous system (CNS) for which there is no clinical treatment. Blood-spinal cord barrier (BSCB) rupture is a critical event in SCI that aggravates nerve injury. Therefore, maintaining the integrity of the BSCB may be a potential method for treating SCI. Here, we showed that patchouli alcohol (PA) exerts protective effects against SCI. We discovered that PA significantly prevented hyperpermeability of the BSCB by reducing the loss of tight junctions (TJs) and endothelial cells. PA also suppressed endoplasmic reticulum stress and apoptosis in vitro. Furthermore, in a rat model of SCI, PA effectively improved neurological deficits. Overall, these results prove that PA exerts neuroprotective effects by maintaining BSCB integrity and thus may be a promising candidate for SCI treatment.